India: Too Many IITs, Unrealistic Expectations - Altbach, Philip; Mathews, Eldho (International Higher Education, 2021)
The Indian Institutes of Technology (IITs), now 23 in number, are the “jewels in the crown” of Indian higher education in terms of quality, international recognition, and producing top graduates. But, in the past several decades, they have overexpanded, and some of them no longer offer top quality education. This article discusses the current condition of IITs and argues that their number should be reduced.